2019
DOI: 10.1002/1873-3468.13438
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐21‐5p regulates mycobacterial survival and inflammatory responses by targeting Bcl‐2 and TLR4 in Mycobacterium tuberculosis‐infected macrophages

Abstract: To date, very little is known about the role of microRNA‐21‐5p (miR‐21‐5p) in Mycobacterium tuberculosis (M.tb)‐infected macrophages. Here, we show that M.tb infection of RAW264.7 and THP‐1 cells increases the expression of miR‐21‐5p. MiR‐21‐5p enhances M.tb survival and apoptosis, and attenuates the secretion of inflammatory cytokines, including interleukin (IL)‐1β, IL‐6, and tumor necrosis factor‐α in M.tb‐infected macrophages. Dual‐luciferase reporter assay revealed that the 3′‐UTR of B‐cell lymphoma 2 (Bcl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 21 publications
(28 reference statements)
2
19
0
Order By: Relevance
“…The same was observed in RAW264.7 and THP-1 cells where miR-21 enhanced M. tuberculosis survival and apoptosis and attenuated the secretion of inflammatory cytokines (IL-1␤, IL-6, and TNF-␣) by targeting B-cell lymphoma-2 (Bcl-2) and Toll-like receptor 4 (TLR4) (Fig. 4A) (107). Finally, miR-21 levels also increased in PPD-MPT64-stimulated RAW264.7 cells in contrast to PPD-stimulated cells, showing that M. tuberculosis immunogenic protein MPT64 upregulates miR-21 due to increased NF-B expression, leading to the upregulation of Bcl-2, an antiapoptotic protein, thus decreasing cell death (Fig.…”
Section: Role Of Validated Mirna In Different Stages Of Diseasesupporting
confidence: 66%
“…The same was observed in RAW264.7 and THP-1 cells where miR-21 enhanced M. tuberculosis survival and apoptosis and attenuated the secretion of inflammatory cytokines (IL-1␤, IL-6, and TNF-␣) by targeting B-cell lymphoma-2 (Bcl-2) and Toll-like receptor 4 (TLR4) (Fig. 4A) (107). Finally, miR-21 levels also increased in PPD-MPT64-stimulated RAW264.7 cells in contrast to PPD-stimulated cells, showing that M. tuberculosis immunogenic protein MPT64 upregulates miR-21 due to increased NF-B expression, leading to the upregulation of Bcl-2, an antiapoptotic protein, thus decreasing cell death (Fig.…”
Section: Role Of Validated Mirna In Different Stages Of Diseasesupporting
confidence: 66%
“…Thus, the non-coding regulators igniting and propagating COVID-19 may provide potential mechanistic explanations to the hazards incurred by at-risk populations, and our findings bring ncRNAs at large, and DANCR and NEAT1 in particular, to the realm of COVID-19 and its aftermath. Further suggestive of the inter-individual risk disparity in COVID-19 is the observed differential expression by sex of several miRs including miR-21-5p, which has been previously observed to be dysregulated and associated with immune function in infectious scenarios ( 151 154 ). In the current study, we also noted sex-related changes in the activity of cholinergic and inflammatory elements, inversely correlated to DANCR’s expression levels.…”
Section: Discussionmentioning
confidence: 76%
“…These studies showed that certain miRNAs are significantly upregulated or down-regulated in inflammation or apoptosis-related diseases, which are concomitant with increased levels of inflammatory cytokines, including IL-1b, IL-6 and TNF-a. 11 Using a LPS-induced mice lung injury model, Cai et al found that miR-214 and miR-451 were significantly up-regulated, while miR-16, miR-23a, miR-24 and miR-199a were obviously down-regulated. In addition, they found miR-16 was involved in regulation of posttranscription of IL-6 and TNF-a in LPS-stimulated A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…19 Zhao et al demonstrated that miR-21 regulated mycobacterial survival and inflammatory responses by targeting Bcl-2. 11 Zhuang et al showed that miR-202 suppressed hepatocellular carcinoma progression via down-regulating Bcl-2 expression. 20 Here, we found that Bcl-2 over-expression reversed miR-21-induced apoptosis and inflammation, and showed synergic effects with miR-21 inhibitor in LPSinduced HPAEpiC.…”
Section: Discussionmentioning
confidence: 99%